(untitled) (Physical Education, Health and Social Sciences, 2025)
Small and medium-sized enterprises (SMEs) increasingly rely on information technology (IT) projects to enhance competitiveness, yet project underperformance remains widespread. This study investigates whether project management methodology—Agile, Hybrid, or Waterfall—significantly influences IT project success in U.S.-based SMEs. Grounded in Success Management Theory (SMT), a quantitative correlational survey was conducted with 165 project managers overseeing IT-supported initiatives. Project success was assessed across five dimensions: budget performance, schedule adherence, scope delivery, quality, and stakeholder satisfaction. Data were analyzed using ANOVA, Pearson correlations, and multiple regression models in SPSS. Findings reveal no statistically significant differences in success across methodologies. Methodology type showed negligible predictive power for budget/time performance (β = 0.043, p = 0.462), scope/quality success (β = 0.058, p = 0.398), and stakeholder satisfaction (β = 0.037, p = 0.521). Overall explanatory power was modest (R²_budget/time = 0.092; R²_scope/quality = 0.107; R²_stakeholder = 0.088). Conversely, contextual factors exhibited stronger predictive value: management support (β_budget/time = 0.321, p < 0.001), goal clarity (β_scope/quality = 0.287, p < 0.001), and stakeholder engagement (β_stakeholder = 0.354, p < 0.001). The results suggest that methodological choice alone does not determine IT project success in SMEs; rather, organizational context, leadership support, and stakeholder alignment are more influential. The study contributes to the application of SMT in IT project environments and offers practical guidance for SME leaders emphasizing methodological fit and organizational readiness rather than reliance on a single project management approach.